2022
DOI: 10.32479/ijeep.12768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drivers and Barriers of Wind Power Generation in Pakistan. SWOT-Delphi Method

Abstract: In the last two decades electricity shortage has hampered the economic growth of Pakistan. To overcome these crises, thermal power plants were commissioned to bridge the supply and demand gap. Deployment of thermal power generation resulted in an unsustainable energy mix with the higher cost of generation. In the last decade, policymakers have shown considerable interest in deploying renewable energy generally and wind energy particularly. Therefore, this paper evaluates some important drivers and barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Concurrently, the second hypothesis focuses on a business that is often marginalised in safety discourse: the air conditioning industry. The combination of data sciences and intelligent technology provides a diverse approach to safety in this context [21]. Predictive analytics and real-time monitoring are reactive procedures that grow into preventative ones to avert possible dangers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, the second hypothesis focuses on a business that is often marginalised in safety discourse: the air conditioning industry. The combination of data sciences and intelligent technology provides a diverse approach to safety in this context [21]. Predictive analytics and real-time monitoring are reactive procedures that grow into preventative ones to avert possible dangers.…”
Section: Resultsmentioning
confidence: 99%
“…The ramifications extend beyond individual industries and hint at a paradigm change in which international cooperation and the sensible use of technology generate a safer, more interconnected society. Recognizing the multilayered complexity of safety in a globalised society, the discourse calls for more thorough study and strategic planning to completely realise these principles [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of energy usage and thermal comfort, this strategy may be very helpful for reaching an agreement on the optimal methods for optimizing both [25].Complex variables, such as building design, materials, climate, user behaviour, and technology advancements, impact energy use in the industrial and commercial sectors. On the other hand, thermal comfort is a state of mind that conveys happiness with the thermal environment and is impacted by variables such as temperature, humidity, air velocity, clothing, and metabolic rate [26]. In this use of the Delphi technique, a panel of experts replies to surveys independently in at least two rounds.…”
Section: Methodsmentioning
confidence: 99%
“…This map unravels that Pakistan has a huge potential for wind energy generation. Bhutto et al [39] have done a SWOT analysis of wind energy generation in Pakistan. The research revealed that Pakistan has a huge potential for wind energy generation.…”
Section: Overviewmentioning
confidence: 99%